« Quels enjeux de nature éthique l’épidémie de COVID 19 a-t-elle soulevé ? » - Aubry, R. (Ethique Sante, 2020)
The COVID-19 epidemic has highlighted or revealed real ethical issues, revealing the limits of knowledge, the limits of life, the limits of our health care system, the limits of our society. Questioning these limits and therefore these ethical issues can be interesting to advance our health system and our society. In this article, we have chosen to address a few ethical questions concerning more particularly the function of care, the relationship to death, the relationship to uncertainty, questions more related to containment measures than to COVID itself and finally a more political questioning on what this epidemic reveals about the fragility of our societies and our economies. We arbitrarily set aside, given the constrained format of the article, some extremely important issues such as research ethics issues, issues related to the notion of patient selection or triage, issues related to the ethics of managing the shortage, and finally issues related to the tracing of contacts or patients.